2022
DOI: 10.1155/2022/8402116
|View full text |Cite
|
Sign up to set email alerts
|

hsa_circ_0003176 Suppresses the Progression of Non-Small-Cell Lung Cancer via Regulating miR-182-5p/RBM5 Axis

Abstract: Background. Non-small-cell lung cancer (NSCLC) is one of the major diseases that threaten human health, and there is still no fundamental treatment method. Emerging evidences suggested that circRNAs might be an effective target to treatment NSCLC. However, the roles and detailed mechanisms of hsa_circ_0003176 in NSCLC still not clear. Methods. hsa_circ_0003176 was identified from GSE101684 and GSE112214 datasets of Gene Expression Omnibus (GEO) database. The expression of hsa_circ_0003176 was detected by RT-qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The function of circRNAs is related to their sequence, stability, post‐transcriptional modification, secondary structure, and the cellular sites where they accumulate 54 . Many studies have reported that circRNAs are localized in the cytoplasm so that they can absorb miRNA 55,56 . Additionally, some circRNAs are localized in the nucleus; for instance, circ‐HuR, which interacts with CNBP to inhibit its binding to HuR promoters, leading to HuR downregulation 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of circRNAs is related to their sequence, stability, post‐transcriptional modification, secondary structure, and the cellular sites where they accumulate 54 . Many studies have reported that circRNAs are localized in the cytoplasm so that they can absorb miRNA 55,56 . Additionally, some circRNAs are localized in the nucleus; for instance, circ‐HuR, which interacts with CNBP to inhibit its binding to HuR promoters, leading to HuR downregulation 57 .…”
Section: Discussionmentioning
confidence: 99%
“… 54 Many studies have reported that circRNAs are localized in the cytoplasm so that they can absorb miRNA. 55 , 56 Additionally, some circRNAs are localized in the nucleus; for instance, circ‐HuR, which interacts with CNBP to inhibit its binding to HuR promoters, leading to HuR downregulation. 57 An intronic circRNA, circ‐CTNNB1, can bind to DDX3, promote its physical interaction with the transcription factor YY1 and regulate transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in both NSCLC tissues and cell lines, hsa_circ_0003176 had the typical characteristics of circRNAs, which were downregulated. Functionally, hsa_circ_0003176 was overexpressed, which prevented NSCLC cells from proliferating, invading other cells, and growing both in vitro and in vivo [ 107 ]. These findings might improve our understanding of the molecular processes behind the development of NSCLC into a malignant state.…”
Section: Implication Of Exosomal Circrna In Lung Cancer Progressionmentioning
confidence: 99%
“…For example, circular pleiotrophin (circPTN) and circRNA C190 have been proven to be oncogenic for NSCLC ( 13 , 14 ). Conversely, circ_0002346 and circ_0003176 have been identified to be tumor suppressors for NSCLC ( 15 , 16 ). However, the expression and function of circ_0087378 has never been researched currently.…”
Section: Introductionmentioning
confidence: 99%